Paternal narratives and the presence of the mother who died - Rigão, Gabriela Sarturi (2023)
This qualitative study aimed to understand, through the father's perspective, how the maternal figure remains present in families with children who have experienced the mother's death. Four widowed men participated, parents of children whose mothers had died. Narrative and semi-structured interviews, as well as drawings, were used as instruments. From the content analysis, the results indicated that the families built narratives that kept the mother's memories and teachings in their lives. The mother's perpetuation as an idealized figure, highlighted by her positive characteristics, remained as a guide to be followed. In the parent-child relationship, the mother was referred to as present through conversations, stories, photographs and the preservation of her teachings.